(untitled) (Letras Clássicas, 2014)
Among the tragic poets, Euripides stands out by the wide use he makes of visual elements in his drama, especially the ekphrasis. Ion, in two moments, shows this quality: in the chorus’ description of the temple of Apollo at Delphi façade (v.184-221), and in the messenger-speech (v.1122-1228). I will concentrate my analysis on the latter, in order to demonstrate how Euripides meant it as a play within the play. Not only does the messenger employ theatrical technical terms, but also the main character in the passage, Ion, arises once as an actor, director and scenographer of the drama that unfolds, distant from the audience eyes, but evidently able to reach their ears.